Kontestasi di Arena Dakwah Kampus: Studi Atas Strategi Aktivis Dakwah Fakultas Dan Kampus Untuk Memobilisasi Sumber Daya Dakwah di Universitas Gadjah Mada - Anggalih Bayu Muh. Kamim; A Naufal Azizi; Dicky Adra Pratama; Luthfian Haekal; Dhimas Ragil S (Jurnal Hikmatuna, 2018)
Islamic da’wah positions have encouraged da'wah activists to mobilize their own modalities to spread what they call the guidance of Islamic character that is the main goal of the da’wah at campus. Excavations on the position of da'wah on campus as a contested and mobilized resource have not been much excavated by academics. This research is a qualitative descriptive research to explain the process of mobilization of da'wah resources conducted by da'wah activists at campus and faculty level at Gadjah Mada University. Data collection was done by in-depth interview and non participant observation. The research results show the role of campus / faculty mosque to be central in the effort of mobilization of "da'wah" resources used by da'wah activists at the faculty and campus level at Gadjah Mada University. The condition of mosque and prayer room at faculty level at UGM in da'wah activity is more fluid and facing the condition of different da'wah object, so there is process of adjustment done by da'wah activist